UPAYA MENINGKATKAN KEMAMPUAN BERBAHASA ANAK DALAM BERCERITA MELALUI METODE TANYA JAWAB USIA 2-4 TAHUN - Novida Aprilina (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2022)
Abstract in English This study aims to improve children’s ability to tell stories through the question and answer method. Not all children can give a response when the storytelling process takes places and not all children are able to convey the meaning of their words well. The purpose of this study to determine the improvement of language skills through storytelling activities through the question and answer method. This study uses the class action research method. The research was conducted in a series of 2 recurring cycles, namely cycle I and cycle II. The four main activities that exist in each cycle are planning, implementation, observation, reflection. Prasiklus data as the foundation of awlany is only 35%. The results of this study indicate an increase in the success of the average percentage in the first cycle of RPPH I is 52,67% increased in the second cycle of RPPH 5 to 78,75% so that the application of storytelling activities with question and answer method can improve children’s language skills exceed the indicator of success that is ≥.76%. The conclusion of this study is that storytelling activities through the question and answer method are able to improve the language skills of the chidren aged 2-4 years at KB Budi Mulia Kediri.